O barroco, o tempo e a morte na narrativa de José Saramago e Autran Dourado - Sibin, Elizabete Arcalá (2017)
The research presented here was centered on reflections on the permanence of the baroque and the fictional representation of time in the novels Memorial of the Convent and The Intermittents of Death by José Saramago and The Bells of Agony and Opera of the Dead by Autran Dourado. From the reading of the novels of these authors, the following questions emerged that guided the study: how do we record the time in the novels mentioned above? What traces from the baroque remain in the memorial of the convent and The flashes of death and in The bells of agony and Opera of the dead? What characteristics approximate and distance the style of José Saramago and that of Autran Dourado? In order to find answers to such questions, a comparison was made between the novels Memorial of the Convent and The Intermittents of Death and The Bells of Agony and the Opera of the Dead, in order to: point out the characteristics of each novel and establish the Approximations and distances between the texts of the two authors; To understand the baroque characteristics present in the mentioned works and the treatment given to the fictional representation of the time. In order to reach the proposed objectives, the reflections of St. Augustine (1984), Paul Ricoeur (1994, 1995 and 1997), Philippe Ariès (2012), Edgar Morin, (1997), Alfredo Bosi (1977) Ana Paula Arnaut (2011), Flávio Kothe (1986), Aguiar e Silva (1976), Irlemar Chiampi (1980 and 1998), Omar Calabrese (1987), among others. It is, therefore, a bibliographical research that made it possible to conclude that both the Memorial of the Convent and The Intermittents of Death and the Bells of Agony and the Opera of the Dead, through the reappropriation of the stylistic resources or thematic approach, promote the permanence of the Baroque in contemporary times. And also because José Saramago and Autran Dourado retake the baroque as a new cultural object, whose innovations are built from the permanence of the style of the eighteenth century, with the purpose of promoting social criticism through the exposition of social problems And the internal conflicts of the characters, it can be said that the authors approach the neo-baroque tendency.